ChemInform Abstract: Noncovalent Interactions in Organocatalysis and the Prospect of Computational Catalyst Design. Issue 28 (June 2016) - Wheeler, Steven E.; Seguin, Trevor J.; Guan, Yanfei; Doney, Analise C.
Abstract: Review: 49 refs.